2018
DOI: 10.3892/ijo.2018.4347
|View full text |Cite
|
Sign up to set email alerts
|

Different splicing isoforms of ERCC1 affect the expression of its overlapping genes CD3EAP and PPP1R13L, and indicate a potential application in non-small cell lung cancer treatment

Abstract: Numerous genes are arranged in complex overlapping and interlaced patterns, and such arrangements potentially contribute to the regulation of gene expression. Previous studies have demonstrated that a region in chromosome 19q13.2-3 encompassing the overlapping genes excision repair cross-complementation group 1 (ERCC1), CD3e molecule associated protein (CD3EAP) and protein phosphatase 1 regulatory subunit 13 like (PPP1R13L) was found to be associated with the risk and prognosis of non-small cell lung cancer (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…In another previous study, we confirmed that co‐expression patterns were consisted in overlapping genes as ERCC1 , CD3EAP, and PPP1R13L. Particularly, there was a significant association between CD3EAP exon 3 and ERCC1 exon 11, while CD3EAP exon 1 and PPP1R13L exon 1 . The potential influence of CD3EAP expression was in response to the regulation of genetic networks known to be associated with DRC and lung cancer risk.…”
Section: Discussionsupporting
confidence: 77%
“…In another previous study, we confirmed that co‐expression patterns were consisted in overlapping genes as ERCC1 , CD3EAP, and PPP1R13L. Particularly, there was a significant association between CD3EAP exon 3 and ERCC1 exon 11, while CD3EAP exon 1 and PPP1R13L exon 1 . The potential influence of CD3EAP expression was in response to the regulation of genetic networks known to be associated with DRC and lung cancer risk.…”
Section: Discussionsupporting
confidence: 77%
“…And then their correlation at the mRNA level in cancer tissues but not in para-cancer tissues was found. Some reports and our previous study confirmed that numerous alternative splicing events occur in ERCC1 , which means different spliceosomes of ERCC1 expressed differently in cancer and para-cancer tissues 22, 33, 34. The difference of the association between AC138128.1 and ERCC1 expression in cancer and para-cancer tissues may be due to the changes in the alternative splicing isoform of ERCC1 expression in cancer and para-cancer.…”
Section: Discussionsupporting
confidence: 62%
“…All detection service was performed by OE Biotech's (Shanghai, China). The method of data standardization has been described previously 22. The upstream and downstream 100k nts of ERCC1 gene is from 45876341 to 46078414 in chromosome 19 (GRCh37).…”
Section: Methodsmentioning
confidence: 99%
“…In other scholars' prognostic analysis of HCC, CD3EAP is also a predictor, suggesting that CD3EAP is an important predictor of HCC prognosis, but the function of CD3EAP is not completely clear (22). The function of GAS2L3 is still unknown; it may be involved in mediating the absorption and clearance of prostaglandins, but it has not reported in liver cancer (13).…”
Section: Discussionmentioning
confidence: 98%